Corrosion processes affecting copper-coated used fuel containers for the disposal of spent nuclear fuel: critical review of the state-of-knowledge - Colleen O. Harper; Julie L. Brown; Richard T. Amos (npj Materials Degradation)
Abstract The uniqueness of the Canadian spent nuclear fuel disposal container design requires a detailed understanding of the copper corrosion processes that could occur in deep geological repositories. This review aimed to identify knowledge gaps surrounding impacts of changing conditions and the evolution of corrosion processes as conditions change from moist/cool, through warm/dry, to cool/fully saturated. This review indicates that early, unsaturated corrosion, and compounding influences of previous corrosion are understudied.